The risk of asthma exacerbation after reducing inhaled corticosteroids: a systematic review and meta‐analysis of randomized controlled trials. Issue 4 (26th February 2014) - Hagan, J. B.; Samant, S. A.; Volcheck, G. W.; Li, J. T.; Hagan, C. R.; Erwin, P. J.; Rank, M. A.
Abstract Background Asthma guidelines suggest reducing controller medications when asthma is stable. Methods The purpose of the study is to estimate the risk of asthma exacerbation in stable asthmatics who reduce inhaled corticosteroids (ICS) compared to those who maintain a stable ICS dose. We identified articles from a systematic review of English and non‐English articles using MEDLINE, EMBASE, Web of Science, and CENTRAL (inception to May 25, 2013). We included randomized controlled trials (RCTs) with a stable asthma run‐in period of 4 weeks or more, an intervention to reduce ICS, and a follow‐up period of at least 3 months. Results The search strategy identified 2253 potential articles, of which 206 were reviewed at the full‐text level and 6 met criteria for inclusion. The relative risk of an asthma exacerbation in individuals who reduced ICS compared to those who maintained the same ICS dose was 1.25 (95% CI 0.96, 1.62; P = 0.10; I2 = 0%) in studies with a mean follow‐up of 22 weeks. Individuals who reduced ICS had a decreased% predicted FEV1 of 0.87% (95% CI −1.58%, 3.33%; P = 0.49, I2 = 58%) and a decreased mean morning peak expiratory flow of 9.57 l/min (95% CI 1.25, 17.90; P = 0.02; I2 = 74%) compared to those individuals who maintained a stable ICS dose. Conclusions Asthma exacerbations were statistically no more likely among individuals who reduced ICS compared to those who maintained their ICS dose, supporting current guidelines which recommend decreasing ICS by 50% after a period of asthma stability.